Over two decades of blended and online physics courses at Michigan State University - Gerd Kortemeyer (FernUniversität Hagen, 2014)
In Fall 1992, our first physics course offered online homework. Over two decades later, we have seven physics courses online, spanning the whole range of introductory course offerings, with a total of over 1600 students in 2014. We found that several of the the purely online courses had better learning success than traditional lecture courses, as measured by exam scores. Particularly successful were online materials with embedded assessment. This result can be interpreted in different ways, but may serve as an indicator that during in-class lectures, we are oftentimes not taking advantage of the fact that we have the students on-site.